Evaluation of breed productivity in Africa and ILCA resources for data analysis - Trail, J.C.M.; Durkin, J.W. (International Livestock Centre for Africa, 1982)
Examines the quantity of past research work and its value in determining the comparative performance of breeds in Africa using cattle as an example. Describes ILCA resources available for analysis and interpretation of field data.